Physical Activity and the Occurrence of Postnatal Depression—A Systematic Review - Kołomańska-Bogucka, Daria (Medicina (Kaunas), 2019)
Background and Objectives: During pregnancy and the postnatal period many changes occur in a woman’s body, both in mental and physical spheres. The birth of a child and a new role—of a mother—can sometimes be associated with numerous negative emotions, uncertainty, fear, anxiety, disgust, depression, or sadness. In the puerperium period, the development of baby blues or postpartum depression may occur. Postpartum depression develops within one month of childbirth and may last up to one year. Depressive disorders that may develop in a young mother affect both her and the newborn’s health. That is why it is so important to try to search for factors that could significantly reduce the likelihood of developing depression in this period. The study aims at assessing the relationship between physical activity during pregnancy and puerperium or in the postpartum and the development of postnatal depression. Materials and Methods: A review of the literature was carried out in the Medline-PubMed database. The search terms were “pregnancy” AND “physical activity AND postpartum depression”. The study included only English-language publications published in the period 2000–2018. Results: A total of 216 references were found. After establishing the inclusion and exclusion criteria based on the analysis of titles and abstracts, 173 articles were excluded from the review. A total of 43 publications were read in full. Finally, 16 articles were included in the review. It was shown that regular physical activity during pregnancy, pregnancy, and puerperium, or in the postnatal period itself as compared to inactivity, reduces the risk of developing depression in pregnant women and after the birth of a child. Conclusions: Physical activity can be an essential factor in the prevention of depressive disorders of women in the postnatal period.